Neuro-imaging in intracerebral hemorrhage: updates and knowledge gaps - Penckofer, Mary; Kazmi, Khuram S.; Thon, Jesse; Tonetti, Daniel A.; Ries, Casey; Rajagopalan, Swarna (Frontiers in Neuroscience, 2024)
Intracerebral hemorrhage (ICH) is characterized by hematoma development within the brain’s parenchyma, contributing significantly to the burden of stroke. While non-contrast head computed tomography (CT) remains the gold standard for initial diagnosis, this review underscores the pivotal role of magnetic resonance imaging (MRI) in ICH management. Beyond diagnosis, MRI offers invaluable insights into ICH etiology, prognosis, and treatment. Utilizing echo-planar gradient-echo or susceptibility-weighted sequences, MRI demonstrates exceptional sensitivity and specificity in identifying ICH, aiding in differentiation of primary and secondary causes. Moreover, MRI facilitates assessment of hemorrhage age, recognition of secondary lesions, and evaluation of perihematomal edema progression, thus guiding tailored therapeutic strategies. This comprehensive review discusses the multifaceted utility of MRI in ICH management, highlighting its indispensable role in enhancing diagnostic accuracy as well as aiding in prognostication. As MRI continues to evolve as a cornerstone of ICH assessment, future research should explore its nuanced applications in personalized care paradigms.